Surfactant-Free Synthesis of Single Crystalline SnS2 and Effect of Surface Atomic Structure on the Photocatalytic Property - Mengyi Li; Enzuo Liu; Huilin Hu; Shuxin Ouyang; Hua Xu; Defa Wang (International Journal of Photoenergy)
Sheetlike tin disulfide (SnS2) single crystal exposed with well-defined {001} facets and flowerlike SnS2 mainly exposed with {010} facets were prepared through a surfactant-free solvothermal process. Photocatalytic degradation of methyl orange (MO) under visible light irradiation indicated that the sheetlike SnS2 showed a much higher activity than flowerlike SnS2. Theoretical and experimental results revealed that the band structure derived from the surface atomic structure played a more important role than the surface energy in the photocatalytic property. The present work has provided a deep insight into the important role of the surface energy and band structure, both of which are derived from the surface atomic structure, in the photocatalytic activity.